Lipid Profile And Carotid Artery Plaque In Ischaemic Stroke Patients (TAJ: Journal of Teachers Association, 2018)
Stroke patients have significant lipid abnormality and it is associated with formation of carotid artery plaque. This is an observational study conducted at the department of Medicine, Rajshahi Medical College Hospital, Rajshahi, to observe the frequency of carotid artery plaque in ischaemic stroke patients and its correlation with dyslipidaemia. Fifty patients of stroke with cerebral infarction confirmed by CT scan of brain were included. The frequency of significant carotid artery plaque was on right side 52%, on left side 40% and on both side 34%. Both Left and right internal carotid artery showed positive correlation with serum total cholesterol, LDL cholesterol and HDL cholesterol but it was not statistically significant (r